Determinants of adverse drug reactions reporting in retail chemists in Nairobi County, Kenya - Njiru, June W.; Mwangi, Eunice M.; Oluoch, Musa (International Journal Of Community Medicine And Public Health, 2020)
Background: Reporting of adverse drug reactions remains the mainstay of a vibrant pharmacovigilance system that seeks to safeguard medicines in a health system. This study sought to establish the impact of the national medicines regulatory body, The Pharmacy and Poisons Board (PPB), the operationalization of pharmacovigilance implementation strategies in the retail chemists, the effect of the capacity and that of underlying motivation factors of the retail chemist personnel on reporting of adverse drug reactions. Methods: This was a descriptive cross-sectional study design conducted between May 2018 to June 2018. Results: 149 (60%) of the respondents stated that PPB did not engage retail chemists as stakeholders in pharmacovigilance, 127 (51%) said they had never read any PPB publication on pharmacovigilance, 151 (61%) said they had general knowledge on pharmacovigilance, receiving feedback from PPB was considered a major motivational factor towards ADR reporting by 237 (96%). Multivariate analysis of the determinants of ADR reporting in retail chemists established that the pharmacovigilance implementation strategies (p<0.026), retail chemist personnel (p<0.001) and underlying motivational factors (p<0.05) had significant influence on ADR reporting in retail chemists in Nairobi County. Conclusions: PPB has not engaged retail chemists on pharmacovigilance matters as key stakeholders and this has impacted the quality of the pharmacovigilance implementation strategies in the chemists as well as the capacity and motivation of the retail chemist personnel to report ADRs.